Achieving Zero Net Land Degradation: Challenges and opportunities. (January 2015) - Stavi, Ilan; Lal, Rattan
Abstract: Land degradation is extensive, covering approximately 23% of the globe's terrestrial area, increasing at an annual rate of 5–10 million ha, and affecting about 1.5 billion people globally. Such detrimental processes call for urgent and comprehensive action to halt land degradation. In this paper, we assess the causes and extent of land degradation around the world, followed by an outline of the various challenges in implementing a global Zero Net Land Degradation (ZNLD) policy. The concept of ZNLD proposes a scheme under which the extent of global degraded lands will decrease or at least, remain stable. To enable this type of scenario, the rate of global land degradation should not exceed that of land restoration. Restoration efforts should include not only croplands, rangelands, and woodlands, but also natural and semi-natural lands that do not generate direct economic revenues. The United Nations Convention to Combat Desertification (UNCCD) envisages achieving this target by 2030. Despite being seemingly ambitious, the target of ZNLD could be achieved if degraded lands are restored to a considerable extent and, at the same time, land-degrading management practices are replaced with ones that conserve soils. To enable effective implementation of these steps, it is necessary to formulate a ZNLD Protocol aimed at managing assessment actions and maintaining of supportive policies and regulations. Restoration projects could be financed through payments for improving ecosystem services, as well as other economic mechanisms. Achieving the target of land degradation neutrality would decrease the environmental footprint of agriculture, while supporting food security and sustaining human wellbeing. Highlights: Degradation of land is widespread, encompassing extensive lands around the world. To enable ZNLD, the rate of global land degradation should not exceed that of land restoration. Restoration should also include natural lands that do not generate direct economic revenues. Policies and regulations should be established for supporting restoration efforts. Financing could be based on payments for the accomplishment of ecosystem services.